Слово о походе Игоревом, Игоря, сына Святославова, внука Олегова - Дмитриев Л. А. Лев Александрович; Лихачев Д. С. Дмитрий Сергеевич; Творогов О. В. Олег Викторович; Рубцов С. С. (Новосибирск, Западно-Сибирское книжное издательство, 1984)
Загл. указано на корешке.